2023
DOI: 10.3390/horticulturae9010082
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Rhododendron liliiflorum H. Lév. Flower Colour Differences

Abstract: Rhododendron liliiflorum H. Lév., with white outer edges and yellow inner edges of petals, is an ornamental flower that originated in China. In this study, we analysed the white (W) and yellow (Y) parts of R. liliiflorum flowers by RNA sequencing. Then, unigene assembly, unigene annotation, and classification of Eukaryotic Orthologous Groups (KOGs) were performed. Gene ontology (GO) classification and pathway enrichment analysis for unigenes were also conducted. A total of 219,221 transcripts and 180,677 unige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…albiflorum and R. dauricum in this pathway, such as PAL, C4H, CHS, CHI, F3H, F3 5 H, DFR, ANR, and UFGT. Similar findings were also observed in comparisons between white flowers and violet and pink flowers in R. pulchrum [40], as well as between white flowers and yellow flowers in R. liliiflorum [41].…”
Section: Anthocyanin Biosynthesis Responsible For White Flower Of R D...supporting
confidence: 85%
“…albiflorum and R. dauricum in this pathway, such as PAL, C4H, CHS, CHI, F3H, F3 5 H, DFR, ANR, and UFGT. Similar findings were also observed in comparisons between white flowers and violet and pink flowers in R. pulchrum [40], as well as between white flowers and yellow flowers in R. liliiflorum [41].…”
Section: Anthocyanin Biosynthesis Responsible For White Flower Of R D...supporting
confidence: 85%
“…The TCA cycle is the primary pathway for ATP production in the body, providing over 90% of the energy required for an organism's life processes [64]. A study by Zhang et al [65] on the effects of the water flow rate stress on the liver of Trachinotus ovatus through metabolomics revealed that, compared to the static water group, both the medium-flow and high-flow groups showed an increase in the pantothenic acid content. This suggested that flow rate stress promotes the TCA cycle in the liver of ovate pomfret, providing energy for their movement through enhanced aerobic respiration.…”
Section: Energy Metabolism Disordermentioning
confidence: 99%
“…The mRNA was isolated by the NEBNext Poly (A) mRNA Magnetic Isolation Module (NEB, E7490). The Illumina NEBNext Ultra RNA Library Prep Kit (NEB, E7530) and NEBNext Multiplex Oligos (NEB, E7500) were used in the cDNA library construction [41]. Finally, the constructed cDNA libraries were sequenced on a flow cell on the Illumina HiSeq™ sequencing platform.…”
Section: Transcriptome Analysismentioning
confidence: 99%